Implementing an Inquiry-Based Learning Model to Deepen Students’ Conceptual Understanding - Hanum, Fida; Sebayang, Alexander; Ariyon, Muhammad; Tarigan, Efrata; Herawati, Ira (Journal La Edusci, 2025)
This study examines the effectiveness of the Inquiry-Based Learning model in enhancing students’ conceptual understanding of the SMAW and GMAW welding processes, an area that remains underexplored in vocational education. The research addresses the gap between the development of procedural skills and the acquisition of conceptual reasoning by investigating whether inquiry-oriented instruction can promote deeper cognitive engagement. A quasi-experimental design was implemented involving two intact groups, with the control group receiving conventional teacher-centered instruction and the experimental group experiencing structured IBL activities. Data were collected through pretests, posttests, observations, and semi-structured interviews, and analyzed using paired-sample and independent-sample t-tests, ANCOVA, effect size calculations, and normalized gain measures. The findings reveal that the experimental group demonstrated a substantial and statistically significant improvement in conceptual understanding compared with the modest gains observed in the control group. The intervention produced a very large effect size and a medium-high normalized gain, indicating strong learning effectiveness. Students exposed to IBL were better able to analyze parameter interactions, interpret defect mechanisms, and connect theoretical principles with laboratory outcomes. Overall, the study provides strong empirical evidence that Inquiry-Based Learning is a highly effective pedagogical approach for strengthening conceptual mastery in welding technology and should be considered for broader integration into vocational curricula.